2013
DOI: 10.5539/elt.v6n9p146
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-Based Study of Malaysian ESL Learners’ Use of Modals in Argumentative Compositions

Abstract: This study attempts to examine the use of English modals in terms of their frequency and functions. For this purpose, Form 4 and College students' argumentative compositions were extracted from the Malaysian Corpus of Students' Argumentative Writing (MCSAW). In order to analyze the data, this study employed discourse analysis and some descriptive statistics by using the WordSmith Tools Version 4.0. The findings of the study showed that Form 4 and College students used can and will more frequently in argumentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Arifin (2018) posited that Malaysian lecturers would assert and position themselves in academic discourse, which explained why the 'will' was frequently observed compared to the other modal expressions. Furthermore, this finding was in line with studies such as Danielsson et al (2023), Ekawati (2019), andKader et al (2013) on the effectiveness of authoritative language in creating a focused learning environment. However, Yang and Tao (2018) have cautioned against the possible suppression of student initiative.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Arifin (2018) posited that Malaysian lecturers would assert and position themselves in academic discourse, which explained why the 'will' was frequently observed compared to the other modal expressions. Furthermore, this finding was in line with studies such as Danielsson et al (2023), Ekawati (2019), andKader et al (2013) on the effectiveness of authoritative language in creating a focused learning environment. However, Yang and Tao (2018) have cautioned against the possible suppression of student initiative.…”
Section: Discussionsupporting
confidence: 88%
“…These studies highlight the complexity of the modal auxiliary system, and the various functions that modal verbs fulfil, from expressing probability and possibility to obligation and permission. Kader, Begi, and Vaseghi (2013) revealed that university students used 'can' and 'will' more frequently in argumentative essays than other modal verbs. In addition, the results showed that the present tense of the modal was used more frequently and that the modal verbs of ability were mostly observed in university students' essays.…”
Section: Lowmentioning
confidence: 99%
“…MCSAW, the Malaysian Corpus of Students' Argumentative Essays (Mukundan & Kalajahi, 2013) is a corpus of 565,500 words which is constructed based on argumentative essays written by secondary school (i.e., Secondary Four and Secondary Five) and first-year college students from four states in Malaysia (i.e., Selangor, Negeri Sembilan, Melaka and Kelantan) (Joharry, 2016). Researching the grammatical and phraseological patterns of the English language written by Malaysian secondary and college learners, a number of studies have been identified to date, using the MCSAW (e.g., Joharry, 2016;Kader et al, 2013;Manokaran et al, 2013). The MCSAW has become the main source of Malaysian written learner data in Joharry's (2016) study which investigates the individual keywords and key lexical bundles that appear in the L2 learner writing by comparing the features of can and we, as well as three to four-word lexical bundles together with their functional categories (i.e., referential, discourse organising and stance), with the native speaker learner writing via LOCNESS.…”
Section: The Mcsawmentioning
confidence: 99%
“…Previous research has often explored the frequency of modal verbs in L2 writing [ [6] , [7] , [8] ]. Although these studies have provided valuable insights into the acquisition of modal verbs by L2 learners, identifying phenomena such as overuse, underuse, and misuse, they often focus primarily on frequency, thereby neglecting the semantic and syntactic functions of these verbs.…”
Section: Introductionmentioning
confidence: 99%